2016
DOI: 10.1111/jce.13094
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Genotype on Structural Atrial Abnormalities and Atrial Fibrillation or Flutter in Arrhythmogenic Right Ventricular Dysplasia/Cardiomyopathy

Abstract: Genotype influences atrial volume and occurrence of AA in ARVD/C. While the incidence of AA is similar in PKP2 mutation carriers and patients with no mutation identified, PKP2 mutation carriers have significantly smaller atria. This suggests a different arrhythmogenic mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…7 Mutation carriers, especially PKP2, had a higher proportion of a history of VT and more inducible fast rate VT. 7 Another study showed the incidence of ATa is similar in PKP2 mutation carriers and noncarriers, PKP2 mutation carriers have significantly smaller atria. 18 Data from our study showed the similar results in ATa, but we found no significant difference in LA size.…”
Section: Main Findingssupporting
confidence: 81%
“…7 Mutation carriers, especially PKP2, had a higher proportion of a history of VT and more inducible fast rate VT. 7 Another study showed the incidence of ATa is similar in PKP2 mutation carriers and noncarriers, PKP2 mutation carriers have significantly smaller atria. 18 Data from our study showed the similar results in ATa, but we found no significant difference in LA size.…”
Section: Main Findingssupporting
confidence: 81%
“…In our cohort, one patient (4%) with AA suffered inappropriate ICD shocks. However, prior studies have reported that inappropriate ICD therapies occur in roughly 30% of patients with ARVC with AA after a mean follow‐up of 5.8 years …”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, however, we did not observe a difference in the incidence of desmosomal mutations between ARVC patients with and without AA. Similar findings were found by Camm et al and Bourfiss et al The latter, studied the influence of genotype on AA in patients with ARVC and they grouped patients by the presence of the desmosomal PKP2 mutation, nondesmosomal phospholamban (PLN) mutation, or no pathogenic mutation. They reported that the incidence of AA was comparable between patients with PKP2 mutations or no mutations, but decreased in patients with the PLN mutation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations